2002
DOI: 10.4049/jimmunol.169.2.1084
|View full text |Cite
|
Sign up to set email alerts
|

Late Pregnancy Suppresses Relapses in Experimental Autoimmune Encephalomyelitis: Evidence for a Suppressive Pregancy-Related Serum Factor

Abstract: Women with multiple sclerosis have significantly diminished disease activity during pregnancy. The purpose of our study was to identify the underlying mechanism for the diminished disease activity. We found that during the period of late pregnancy there is protection against paralysis, during both the induction and effector phases of relapsing experimental autoimmune encephalomyelitis, a mouse model of multiple sclerosis. We did not find any changes in the cytokine secretion profiles or the proliferative activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 36 publications
4
64
0
Order By: Relevance
“…Pregnancy also importantly affects the clinical course of MS. Relapse rate significantly declines during the third trimester of pregnancy but considerably increases in the first 3 mo after delivery, if compared with prepregnancy rates (4,5). Similarly to human disease, pregnancy suppresses clinical symptoms of experimental autoimmune encephalomyelitis (EAE), an animal model for MS (6,7), and induction of chronic EAE in the postpartum period results in enhanced mortality and slightly worsened severity (7). Among sexrelated factors, hormones have been hypothesized to play an important role in regulating MS and EAE (3).…”
Section: Ultiple Sclerosis (Ms) Is An Inflammatory Demyelin-mentioning
confidence: 99%
“…Pregnancy also importantly affects the clinical course of MS. Relapse rate significantly declines during the third trimester of pregnancy but considerably increases in the first 3 mo after delivery, if compared with prepregnancy rates (4,5). Similarly to human disease, pregnancy suppresses clinical symptoms of experimental autoimmune encephalomyelitis (EAE), an animal model for MS (6,7), and induction of chronic EAE in the postpartum period results in enhanced mortality and slightly worsened severity (7). Among sexrelated factors, hormones have been hypothesized to play an important role in regulating MS and EAE (3).…”
Section: Ultiple Sclerosis (Ms) Is An Inflammatory Demyelin-mentioning
confidence: 99%
“…Pregnancy and hormones associated with pregnancy exert a protective effect on disease course (12)(13)(14). Pregnant animals showed less severe disease than nonpregnant mice (14,15), and treatment at disease onset with estriol inhibited the severity of passively induced EAE (16).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…Data about clinical improvement of EAE during pregnancy are also highly consistent [42,[49][50][51][52]. Earlier studies could not find any histopathological differences between virgin and pregnant mice with EAE [49,50], but a succeeding investigation found reduced CNS demyelination and cell infiltration during late pregnancy in animals with preinduced EAE [51]. Later on, an elegant experiment of Haghmorad et al [52] has confirmed that pregnancy-induced alleviation of clinical manifestations is accompanied by reduced CNS demyelination and cell infiltration.…”
Section: Influence Of Gender and Sex Hormones On Eaementioning
confidence: 67%
“…Numerous studies using rats, rabbits, guinea pigs, and SJL mice have confirmed that pregnancy reduces the incidence of the disease and/or delays the day of onset [46][47][48][49][50]. Data about clinical improvement of EAE during pregnancy are also highly consistent [42,[49][50][51][52].…”
Section: Influence Of Gender and Sex Hormones On Eaementioning
confidence: 75%
See 1 more Smart Citation